Psychometric properties of the Maslach Burnout Inventory-GS in a Venezuelan sample - Millán de Lange, Anthony Constant (2012)
The assessment of work stress is one of the most important aspects in the current scope of occupational psychological health, especially when it comes to chronic levels of involvement. Here are the results of the Venezuelan psychometric validation of the Cuban version of the Maslach Burnout Inventory-General Survey (MBI-GS). Results show adequate reliability of the instrument and suggest the need to remove item 1 to ensure its construct validity. Some indicators reveal the divergent criterion validity of the MBI-GS on the degree of the participant’s psychological well-being.